2008
DOI: 10.1038/emboj.2008.148
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting β-ring assembly pathway of the mammalian 20S proteasome

Abstract: The 20S proteasome is the catalytic core of the 26S proteasome. It comprises four stacked rings of seven subunits each, a 1-7 b 1-7 b 1-7 a 1-7 . Recent studies indicated that proteasome-specific chaperones and b-subunit appendages assist in the formation of a-rings and dimerization of halfproteasomes, but the process involved in the assembly of b-rings is poorly understood. Here, we clarify the mechanism of b-ring formation on a-rings by characterizing assembly intermediates accumulated in cells depleted of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
217
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(233 citation statements)
references
References 33 publications
12
217
1
3
Order By: Relevance
“…Half-CPs then dimerize on the incorporation of b7 to form mature CPs, accompanied by cleavage of b-subunit propeptides and degradation of UMP1 and PAC1-PAC2 ( Supplementary Fig. S1) 14,26,[31][32][33][34][35][36] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half-CPs then dimerize on the incorporation of b7 to form mature CPs, accompanied by cleavage of b-subunit propeptides and degradation of UMP1 and PAC1-PAC2 ( Supplementary Fig. S1) 14,26,[31][32][33][34][35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…2f). PAC3 is associated with a-rings and detaches from them on b3 recruitment 36 . A small amount of PAC3 was already observed in the intermediates by b7 knockdown, which in principle halts the CP assembly just before b7 incorporation, suggesting that such intermediates are unstable and that some of the already incorporated b-subunits detach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The α subunits www.nature.com/aps Sun P et al Acta Pharmacologica Sinica npg maintain the structure, whereas the core β rings contains the three proteolytically active β subunits [32] . Notably, previous studies reported that the active proteasome β subunits exist in an immature precursor form before being assembled into the integral 26S proteasome [33][34][35][36][37] . The β subunits mature once the proteasome assembles [38,39] .…”
Section: Discussionmentioning
confidence: 99%